Les années 80 et l’épanouissement de l’autofiction : Annie Ernaux et alii - Romeral, Francisca (2018)
The evolution and diversity of news forms of autobiography, especially that of autofiction or self-fiction, characterize 80’s French literature. The adoption of individualistic attitudes and influence of media, promote the emergence of a generation of young writers, including Annie Ernaux, concerned about the capitalization of their life experience and dialogue with their audience and readers. Current literary productions seem to show that, far from being a temporary fad, autofiction asserted itself and conquered other arts.